2018
DOI: 10.1371/journal.pone.0203404
|View full text |Cite
|
Sign up to set email alerts
|

SMAD1/5 signaling in osteoclasts regulates bone formation via coupling factors

Abstract: Bone remodeling occurs via coupling between bone resorption by osteoclasts and bone formation by osteoblasts. The mechanisms that regulate osteoclast signals to osteoblasts are not well understood. Published studies have reported that BMP signaling in osteoclasts regulate osteoclast coupling targets. To investigate the necessity of canonical BMP signaling on osteoclast differentiation and coupling, we mated Smad1fl/fl; Smad5fl/fl mice to c-Fms-Cre mice. We analyzed male mice at 3 months of age to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…(64) Vice versa, BMP signaling in osteoclasts also appears to alter osteoblast function as inhibited SMAD1/5 signaling in osteoclasts has been shown to increase osteoblast activity via osteoclast-to-osteoblast coupling factors such as WNT1, gap junction alpha-1 protein, and sphingosine kinase 1. (65) Finally, recent reports indicate tight connections between BMP and Wnt signaling. (40,66) in vitro blockade of the BMP pathway reversed T 3 -stimulated Dkk1 expression but did not alter the expression of Wnt target genes Axin2 nor Opg, suggesting additional mechanisms might obstruct Wnt signaling in osteoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…(64) Vice versa, BMP signaling in osteoclasts also appears to alter osteoblast function as inhibited SMAD1/5 signaling in osteoclasts has been shown to increase osteoblast activity via osteoclast-to-osteoblast coupling factors such as WNT1, gap junction alpha-1 protein, and sphingosine kinase 1. (65) Finally, recent reports indicate tight connections between BMP and Wnt signaling. (40,66) in vitro blockade of the BMP pathway reversed T 3 -stimulated Dkk1 expression but did not alter the expression of Wnt target genes Axin2 nor Opg, suggesting additional mechanisms might obstruct Wnt signaling in osteoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the comprehensive knowledge about BMP signaling in osteoblasts, its role in osteoclast formation has long been underrated. Several studies report on the endogenous expression of several BMP ligands (BMP1, BMP2, BMP4, BMP6, BMP7), SMAD proteins (SMAD1/5, SMAD4), and BMP receptors (BMPR1A, BMPR1B, BMPR2) in osteoclasts or osteoclast-like cell lines ( Anderson et al, 2000 ; Garimella et al, 2008 ; Jensen et al, 2010 ; Broege et al, 2013 ; Tasca et al, 2015 , 2018 ).…”
Section: Bmp Signaling In Osteoclasts: What Cell Studies and Mouse Momentioning
confidence: 99%
“…Downstream of receptors, in vitro genetic ablation of SMAD1/5 or SMAD4 in osteoclast precursors led to the formation of fewer and smaller multinucleated osteoclasts and to a reduction of resorption pits and resorbed areas ( Tasca et al, 2015 ). Correspondingly, mice with a conditional Smad1/5 knockout in osteoclast precursors (Smad1 fl/fl ;Smad5 fl/fl ;c-Fms-Cre mice, 12-week-old, male) showed mild bone gain due to reduced bone resorption and stimulated bone formation ( Tasca et al, 2018 ). In contrast, Smad4 deletion in mature osteoclasts (Smad4 fl/fl ;Ctsk-Cre mice, 8-week-old, female) increased osteoclast formation and bone resorption leading to an osteopenic phenotype, however, caused by disrupted TGFβ signaling and independent of the BMP pathway ( Morita et al, 2016 ).…”
Section: Bmp Signaling In Osteoclasts: What Cell Studies and Mouse Momentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the generally accepted role of BMPs in osteogenesis, several studies have shown that BMP signaling is also important for osteoclast formation. Inhibition of this signaling, either via deletion of BMPR2 (33) or by inhibiting SMAD 4 or SMAD 1/5 (34,35) reduces DC-STAMP expression and inhibits osteoclastogenesis. Similarly, the inhibitory effect of Activin-A on BMP signaling could be the cause of the inhibited osteoclastogenesis seen in this study.…”
Section: Discussionmentioning
confidence: 99%